As I lay dying. - Faulkner, William (New York. Vintage Books., 1930)
As I Lay Dying is Faulkner$1 (Bs harrowing account of the Bundren family$1 (Bs odyssey across the Mississippi countryside to bury Addie, their wife and mother. Narrated in turn by each of the family members$1 (Bincluding Addie herself$1 (Bas well as others the novel ranges in mood, from dark comedy to the deepest pathos. Considered one of the most influential novels in American fiction in structure, style, and drama, As I Lay Dying is a true 20th-century classic. s
Includes bibliographical references.
86346
Keywords: American literature; Classic literature--American.; Faulkner, William; Ronald Regan